The Effectiveness of Honey Administration on Reducing the Frequency of Diarrhea in Children with Acute Gastroenteritis in the Carnation Room of Rsud Waled Cirebon District: Case Study - Herlina; Syaripudin, Ahmad; Pujiyana; Okta, Ira Rahayu; Hidayat, Lalu Rahmatullah (Jurnal Multidisiplin Madani, 2024)
One of the causes of death in children is diarrhea. Diarrhea is an increased frequency of bowel movements and occurs more than 3x and with a soft and watery consistency due to the water content in the stool >200 ml / 24 hours which lasts < than 14 days. The purpose of this study is to determine the effectiveness of giving honey to reduce the frequency of diarrhea in children. Method: The method uses a qualitative approach with case studies as the main method. Data collected through interviews, documentation, data analysis to the provision of intervention and evaluation. The research was conducted in the Carnation Room of Waled Hospital, Cirebon Regency in February 2024. The sample in this study was children treated with a diagnosis of acute gastroenteritis that focused on nursing problems, namely diarrhea. Honey intervention 3 times / day is given as much as 5 ml / 6 hours to children. Results: based on research that has been done researchers found that giving honey can reduce the frequency of diarrhea in children because of the content in honey